2021
DOI: 10.1021/acs.iecr.1c03800
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients from an Equation of State: Novel Approach for Fast Phase Equilibrium Calculations

Abstract: Deviation from ideal solution behavior is due to differences in intermolecular interactions, e.g., molecular size, shape, dispersion, multipolar, and hydrogen bonding interactions. Activity coefficients characterize deviations from ideal solution behavior; however, most activity coefficient models lack the physics to explicitly account for intermolecular forces such as hydrogen bonding and multipolar interactions. At the same time, molecular theories (in the form of equations of state) that explicitly account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 70 publications
(92 reference statements)
0
25
0
Order By: Relevance
“…of Fouad et al 19 and Chapman and Fouad. 33 The good results of the false VLLE calculations by the UNIQUAC model are also shown in Figure 7. Also, the NRTL model with adjustable parameters does not explicitly account for specific chemical associations such as hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…of Fouad et al 19 and Chapman and Fouad. 33 The good results of the false VLLE calculations by the UNIQUAC model are also shown in Figure 7. Also, the NRTL model with adjustable parameters does not explicitly account for specific chemical associations such as hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
“…If the values of k ij and k A i B j are provided as a result of fitting against experimental data of two nonassociating solvents, this implies that the cross-association does occur. Chapman and Fouad 33 showed that the phase behavior of solvating systems is dominated by cross-associating interactions between unlike species so that the solvation parameters were fitted to the experimental data. The conceptual representation of the PC-SAFT interaction parameters between 62 ICH-reviewed solvents is represented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To appreciate the connection between activity models and EOSs based on TPT1, the expansion rule provides thermodynamically consistent terms for individual contributions, as shown by eq . , An especially convenient assumption is constant packing fraction for all compositions and compounds. This leads to variation of the pressure, of course, but repulsive (rep) terms usually go to zero in that reference frame, helping to focus on the more interesting effects.…”
Section: Models In Current Engineering Practice and Association Theorymentioning
confidence: 99%